A randomized trial of oral versus topical trimethroprim-sulfamethoxazole in the treatment of chronic suppurative otitis media - Acuin, Jose M.
OBJECTIVES: To compare the effectiveness of oral versus topical forms of trimethoprimsulfamethozasole (TMP-S) for the treatment of chronic suppurative otitis media (CSOM) . SETTING: Tertiary care hospital in a periurban community. DESIGN: Randomized clinical trial. PARTICIPANTS: Patients consulting for ear discharge persistent for at least 2 weeks duration and at least 20% central tympanic perforations. SAMPLE SIZE: 102 subjects (51 per group) were deemed adequate for a 2-tailed test with a error=0.05 and a power of 78% to demonstrate a 20% difference in effectiveness (50% for oral TMP-S; 78% for topical TMP-S). OUTCOME MEASURES: Proportions of patients with disappearance of ear discharge , with improvement of middle ear mucosa, and with reduction of the size or closure of the tympanic membrane perforation; percent of discharge-free visits; time to first discharge-free visit; proportions of patients who develop adverse drug reactions and recurrence of discharge; compliance rates. Outcomes were measured at 2,4,8, and 12 weeks after start of treatment in a standard unblinded way. INTERVENTIONS: Oral TMP-S given at 4 and 8 mg/kg/day for children and as 400mg caosules for adults twice daily for at least two weeks or 200 mg of TMP-S powdeer insufflated into the ear canal once daily for at least two weeks; aural toilet by instillation of hydrogen peroxide and dry mopping. RESULTS: 72 patients were evaluated after 90 have been enrolled. There were 41 males with a mean age of 19 years (SD=7; median, 12). The mean duration of ear discharge was 11 years (SD=13); median 6) On all follow-up visits , more patients in the topical group (from 17% to 56%) than in the oral group (from 0% to 33%) had disappearance of discharge. As a whole, 28/42 patients (66%) in the topical group and 11/30 patients (37%) in the oral group experienced at leased one discharged-free visit (p=0.01;adjusted OR=1.83; 95% CI=1.08-3.07). It took 4 weeks (SD=0.02) in the topical group and 6 weeks (SD=0.3) in the oral group before discharge disappeared (p=0.01). Mean perforation sizes were 6 mm(SD=2) for topical and 5 mm(SD=3) for oral group at 8 and 12 weeks. Recurrence rates were 24% and 17% (p=0.66) and compliance rates were 80% and 79% (p=0.92) for topica;l and oral group, respectively, One patient in the oral group developed skin rashes. CONCLUSIONS: Topical TMP-S may be more effective than oral TMP-S in the short-term treatment of CSOM in terms of disappearance of ear discharge and improvement of middle ear mucosa. However, the benefits and risks of its long-term use must still be determined.
Theses--(MS in Epidemiology-Clinical Epidemiology) University of the Philippines Manila
Keywords: Otitis Media, Suppurative